A study to assess the impact of appropriate intervention/s on compliance w.r.t. key hospital infection control parameters in dialysis unit of a tertiary healthcare teaching institute in India - Rajesh Harsvardhan; Ruchi Kushwaha; Richa Mishra; Narayan Prasad (Wolters Kluwer -Medknow Publications, 2023)
Aim: The aim of this study was to assess the impact of appropriate interventions on key infection control parameters subsequent to baseline assessment in dialysis unit with objectives to ascertain the current status of knowledge, attitude, and practice for key hospital infection control (HIC) parameters, to develop and execute appropriate interventions, to assess the impact of interventions, and to recommend an evidence-based HIC module. Methodology: An interventional, longitudinal study was conducted from April 2018 to May 2019 in dialysis unit of SGPGI. Study samples were nurses and technicians. The questionnaire was designed to assess knowledge and attitude. To evaluate practices, a checklist was drafted and graduated by scoring from 0 to 10. Interventions made were on-site training and workshop, IEC, and placement of alcohol-based hand rub. Data analysis was done by SPSS 23. For normally distributed data of the study, Descriptive Statistics was presented in the form of mean ± 2 standard deviation. Paired Sample t-test was used to compare the mean score and Chi Square test was used to compare the Knowledge between pre and post-intervention. Results: The overall improvement in knowledge was from 55% to 70% (P = 0.017-0.000). For attitude, the mean scores changed from 4.61 ± 0.562, 4.63 ± 0.582, 4.40 ± 0.756, and 4.36 ± 0.889 to 69 ± 0.493, 4.76 ± 0.428, 4.73 ± 0.449, and 4.64 ± 0.621. Regarding practices, prior to intervention, the mean scores were 20.49 ± 5.699, 48.75 ± 18.185, 63.25 ± 22.376, and 23.03 ± 10.036, and following intervention, it was found to be 22.98 ± 6.614 (2.49% increase, t = −2.990; P = 0.004), 52.81 ± 19.074 (4.06% increase, t = −1.473; P = 0.145), 68.00 ± 21.955 (4.75% increase, t = −1.472; P = 0.145), and 31.06 ± 13.400 (8.03% increase, t = −4.270; P = 0.000). Conclusions: Hemodialysis patients are vulnerable to severe infections for many reasons in dialysis setting including the failure to comply with appropriate hand hygiene, contamination of the instrument, or improper disinfection practices.